Identification of functional and diverse circulating cancer‐associated fibroblasts in metastatic castration‐naïve prostate cancer patients - Richell Booijink; Leon W. M. M. Terstappen; Eshwari Dathathri; Khrystany Isebia; Jaco Kraan; John Martens; Ruchi Bansal (Molecular Oncology)
In prostate cancer (PCa), cancer‐associated fibroblasts (CAFs) promote tumor progression, drug resistance, and metastasis. Although circulating tumor cells are studied as prognostic and diagnostic markers, little is known about other circulating cells and their association with PCa metastasis. Here, we explored the presence of circulating CAFs (cCAFs) in metastatic castration‐naïve prostate cancer (mCNPC) patients. cCAFs were stained with fibroblast activation protein (FAP), epithelial cell adhesion molecule (EpCAM), and receptor‐type tyrosine‐protein phosphatase C (CD45), then FAP+EpCAM− cCAFs were enumerated and sorted using fluorescence‐activated cell sorting. FAP+EpCAM− cCAFs ranged from 60 to 776 (389 mean ± 229 SD) per 2 × 108 mononuclear cells, whereas, in healthy donors, FAP+ EpCAM− cCAFs ranged from 0 to 71 (28 mean ± 22 SD). The mCNPC‐derived cCAFs showed positivity for vimentin and intracellular collagen‐I. They were viable and functional after sorting, as confirmed by single‐cell collagen‐I secretion after 48 h of culturing. Two cCAF subpopulations, FAP+CD45− and FAP+CD45+, were identified, both expressing collagen‐I and vimentin, but with distinctly different morphologies. Collectively, this study demonstrates the presence of functional and viable circulating CAFs in mCNPC patients, suggesting the role of these cells in prostate cancer.